2002
DOI: 10.1046/j.1365-3156.2002.00914.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and sustainability of a footcare programme in preventing acute attacks of adenolymphangitis in Brugian filariasis

Abstract: SummaryLymphatic filariasis is associated with considerable disability related to the intensity and frequency of acute adenolymphangitis (ADL) attacks. The global programme for elimination of lymphatic filariasis emphasizes the need to combine transmission control with alleviation of disability. Footcare aimed at the prevention of secondary bacterial infections is the mainstay of disability alleviation programmes. We evaluated the efficacy and sustainability of an unsupervised, personal footcare programme by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 8 publications
2
59
0
Order By: Relevance
“…51 The improvement of lymphedema observed in this cohort during this 13-year period clearly coincided with results of the lymphedema management study during 1995-1998. Consistent with other literature is the significant decrease in ADL episodes 14,16,17,20 and the decrease in foot and ankle circumference observed during the lymphedema management program. 20 In addition, the improvement in quality of life associated with lymphedema management programs is consistent with previous findings.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…51 The improvement of lymphedema observed in this cohort during this 13-year period clearly coincided with results of the lymphedema management study during 1995-1998. Consistent with other literature is the significant decrease in ADL episodes 14,16,17,20 and the decrease in foot and ankle circumference observed during the lymphedema management program. 20 In addition, the improvement in quality of life associated with lymphedema management programs is consistent with previous findings.…”
Section: Discussionsupporting
confidence: 90%
“…12 Clinical and histopathologic studies suggest that lymphedema management can decrease the number of ADL episodes 9,[13][14][15][16][17][18][19] and halt or, in some cases, partially reverse disease progression. 14,[16][17][18]20 Although there are several studies demonstrating improvement in lymphedema in patients who adhere to a lymphedema management regimen, the literature exploring the effect of mass drug administration with DEC, either alone or in combination with albendazole, on filarial morbidity is inconclusive. Recent clinical research using ultrasonography and lymphoscintigraphy has documented the reversal of early lymph-vessel damage in Brugia malayi-infected children after MDA with DEC in India.…”
Section: Introductionmentioning
confidence: 99%
“…During the course of research activities in a Brugia malayi endemic area at the Filariasis Chemotherapy Unit in TD Medical College Hospital, Alappuzha, India it was observed that among the asymptomatic, mf-positive subjects screened *30% were aged 420 years, while 16·3% were <10 years. In a study on prevention of ADLA attacks in brugian filariasis, 32% of the adults who had lymphoedema of several years duration recalled during their interview, that their disease first manifested before they were 15 years of age (Suma et al 2002).…”
Section: Y M P H a T I C F I L A R I A S I S I N C H I L D R E Nmentioning
confidence: 99%
“…This lymphatic pathology in infected children, since it is known to persist, might pave way for future development of disease manifestations. In a study on prevention of ADLA attacks in adult patients with filarial lymphedema, during their interview 32% of the subjects recalled that the disease first manifested before they were15 yr of age [36].…”
Section: Filarial Disease Manifestations In Childrenmentioning
confidence: 99%
“…Several studies substantiate the role of proper 'localhygiene' of the affected limbs, carried out regularly, in preventing ADLA [12,25,31]. Foot care aimed at prevention of fungal and bacterial infections has become the mainstay for disability alleviation in GPELF [36,40]. This procedure requires only the common facilities available for washing in any household and hence can be carried out by the patients themselves in their homes.…”
Section: Prevention Of Adlamentioning
confidence: 99%